2017
DOI: 10.1016/j.jaap.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Structure-reactivity relationship in pyrolysis of plastics: A comparison with natural polymers

Abstract: Highlights• Global activation energy depends on conversion in pyrolysis of all polymers.• Activation energy variability is proportional to chemical complexity of polymers.• An Evans-Polanyi relationship for initiation reactions of polymer pyrolysis is proposed. AbstractRecent advances in plastics recycling confirm the high potential of pyrolysis technologies to enhance recovery and selectivity rates. Modelling the kinetics of this complex process to stimulate scaling-up opportunities remains a major challenge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 94 publications
2
4
0
Order By: Relevance
“…In the TGA curve of recycled polyester (Figure 2), one main peak has occurred representing the weight loss with respect to the increase in temperature. Highly oxygenated bonding was responsible for one stage degradation of polyesters [46]. The structural breakdown of recycled polyester fabric has started about 385 • C and the maximum weight loss has occurred at 436.5 • C. About 70% of the weight loss has completed at 440 • C. This data is in correspondence with the TGA data given for thermoplastic decomposition [28,47].…”
Section: Discussionsupporting
confidence: 81%
“…In the TGA curve of recycled polyester (Figure 2), one main peak has occurred representing the weight loss with respect to the increase in temperature. Highly oxygenated bonding was responsible for one stage degradation of polyesters [46]. The structural breakdown of recycled polyester fabric has started about 385 • C and the maximum weight loss has occurred at 436.5 • C. About 70% of the weight loss has completed at 440 • C. This data is in correspondence with the TGA data given for thermoplastic decomposition [28,47].…”
Section: Discussionsupporting
confidence: 81%
“…The most important operating parameters may include the temperature at which pyrolysis is performed, as well as the activation energy (Ea) as a function of the parameters of the biomass components. As already confirmed by the studies of Carrier et al, Larrain et al, and Várhegyi [11][12][13], the evolution of Ea as a function of the degree of advancement shows a dependence of the cellulose rupture mechanism on the process temperature. Thus, it has been suggested that weak bond scission represents the rate-limiting radical generation step in the pyrolysis process.…”
Section: Introductionsupporting
confidence: 61%
“…The reactivity of these mixtures towards pyrolysis conditions are interpreted based on the following devolatilization patterns (Fig. 5): number of DTG peaks, shift of onset temperatures and peak temperature, maximum decomposition temperature and associated decomposition rate [130].…”
Section: Influence Of Blend Ratios On 'Reactivity'mentioning
confidence: 99%